CONSERVATIVE SURGERY IN THE COMPLEX TREATMENT FOR EARLY BREAST CANCER - M. S. Pirogova; V. P. Letyagin; S. B. Peterson (Опухоли женской репродуктивной системы)
Particularities of various types of breast-conserving surgery in the framework of complex treatment of early breast cancer are discussed. Combined modality (breast-conserving surgery combined with radiotherapy) is preferred: it makes possible to reach favorable long-term results. Implementation of this approach allows most patients to rehabilitate in short period of time and to return to adequate life style.